SIGNIFICANCE OF MONOCYTE CHEMOATTRACTANT PROTEIN-1, THYROID HORMONES AND OTHER CLINICAL MANIFESTATIONS IN IRAQI PATIENTS WITH POLYCYSTIC OVARIAN SYNDROME - Raoof, Israa Burhan; Daoud, Aseel Ghassan; Mohsin, Raghad Abdulmahdi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Polycystic ovarian syndrome (PCOS) is a complex disease occurred throw genital period of women depends on the age, genetic factors, and ethnicity. Monocyte Chemoattractant Protein-1 (MCP-1) has been implicated in the metabolic disturbances and menstrual irregularities. Methods: In the biochemical test, the blood was collected in plain tubes then separated by centrifugation. Serum was collected in test tubes then, MCP, haemoglobin (Hb), packed cell volume (PCV), fasting blood glucose (FBG), urea, creatinine, prolactin, testosterone, luteinizing hormone (LH), follicle stimulating hormone (FSH), T3, T4, and thyroid-stimulating hormone (TSH) were determined by enzyme-linked immune-sorbent assay and relevant clinical features were collected simultaneously in all subjects. Results: The results showed no significant increased in means of age, body mass index in PCOS women (patients) when compared with healthy subjects (control groups) also there was no significant decreased in levels of Hb, PCV while increased in FBG, urea and creatinine in PCOS women when compared with healthy subjects. In addition, mean of LH and 17 Î²-Estradiol were no significant increased except the significantly increased in the ratio of LH/FSH, prolactin, and testosterone, while FSH was significantly decreased in PCOS women when compared with healthy subjects. Levels of triiodothyronine (T3) and thyroxine (T4) were found significantly decreased while an increased level of TSH when compared with healthy subjects. Finally, MCP-1 was showed significantly increased in PCOS women when compared with healthy subjects. Conclusions: It can be concluded that PCOS women might suffer from changes in the levels of MCP-1(an inflammation marker). Besides, it was detected that TSH might be responsible related metabolic disturbances could be related to TSH and MCP which can be considered as relevant features in such disturbances.